2023
DOI: 10.1093/nar/gkad216
|View full text |Cite
|
Sign up to set email alerts
|

RNA interactome capture in Escherichia coli globally identifies RNA-binding proteins

Abstract: RNA-binding proteins (RPBs) are deeply involved in fundamental cellular processes in bacteria and are vital for their survival. Despite this, few studies have so far been dedicated to direct and global identification of bacterial RBPs. We have adapted the RNA interactome capture (RIC) technique, originally developed for eukaryotic systems, to globally identify RBPs in bacteria. RIC takes advantage of the base pairing potential of poly(A) tails to pull-down RNA–protein complexes. Overexpressing poly(A) polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…We also recovered proteins involved in metabolic processes, consistent with prior RBP discovery studies that suggested that many metabolic enzymes moonlight as RBPs (45,60). For example, we find that the acyl carrier protein AcpP, which has a crucial role in bacterial fatty acid synthesis, was recovered by the majority of F. nucleatum sRNA baits.…”
Section: S Rna-rnap Complex Formation Is Conserved In F Nucleatumsupporting
confidence: 66%
See 1 more Smart Citation
“…We also recovered proteins involved in metabolic processes, consistent with prior RBP discovery studies that suggested that many metabolic enzymes moonlight as RBPs (45,60). For example, we find that the acyl carrier protein AcpP, which has a crucial role in bacterial fatty acid synthesis, was recovered by the majority of F. nucleatum sRNA baits.…”
Section: S Rna-rnap Complex Formation Is Conserved In F Nucleatumsupporting
confidence: 66%
“…For example, we find that the acyl carrier protein AcpP, which has a crucial role in bacterial fatty acid synthesis, was recovered by the majority of F. nucleatum sRNA baits. Curiously, the AcpP protein was also listed as a strong RBP candidate in E. coli based on analysis of the RNA bound proteome using global methods, such as TRAPP (total RNA-associated protein purification) (61) and RIC (RNA-interactome capture) (60). These observations suggest that AcpP may serve as an RBP in different bacteria, in addition to its core function in fatty acid biosynthesis.…”
Section: S Rna-rnap Complex Formation Is Conserved In F Nucleatummentioning
confidence: 99%
“…We used PNK assays 33 to test in vivo the RNA-binding capacity of proteins from two subgroups shown in Fig. 3d; proteins shifting with high SVM scores (putative new RBPs) and proteins shifting but with low SVM scores (RNA-associated proteins).…”
Section: Resultsmentioning
confidence: 99%
“…The PNK assays were carried out as previously described 33 with some modifications. 400 mL of cultures from reporter strains expressing 3xFLAG protein fusions were grown in BG11 supplemented with the appropriate antibiotic until they they reached a concentration of 2.5 µg chlorophyll/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Since this technique specifically detects proteins bound to eukaryotic messenger RNAs, it is unsuitable to examine RBPs recognising transcripts lacking (long) poly-A tails (e.g., eukaryotic ribosomal, transfer and small nucleolar RNAs as well as prokaryotic transcripts in general). However, this issue can be overcome by transiently overexpressing a poly-A polymerase (Stenum et al, 2023).…”
Section: Defining Microb Ial Rb Pomes: Pha Se-separ Ation Versus Sili...mentioning
confidence: 99%